Employment in social enterprises within the typology of employment models for people with disabilities - Uršič, Anja (Teorija in praksa, 2022)
On the basis of a systematic review of the literature, this article addresses the issue of employment of people with disabilities and analyzes current trends in disability employment to classify employment in social enterprises in the typology of employment models for people with disabilities. For the purpose of classification, the article also identifies individual models of disability which coincide with the characteristics of employment in social enterprises. The upgraded typology is the main contribution of the article; it could serve as an important classification tool for individual approaches to this issue, and thus help to develop appropriate policies for the employment of people with disabilities through a comparative analysis of individual countries
Keywords: Invalidi; Invalidnost; politika zaposlovanja; Socialna podjetja; socialno zaposlovanje; Trg dela; zaposlovanje